Ahl Al-Hadith dan Ahl Al-Ra’y: Dari Konstruksi Metodologi Hingga Tipologi Pemahaman Hadis Dialektik - Munawir, Munawir (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
The complexity of the Prophetic traditions is not only related to the validity of the sanad and matn, but also to the socio-historical setting that lies behind the text of a hadith, even also the psychology of the Prophet himself. Amidst the complexity, there are two large groups which have different construction of understanding and tend to be in conflict, namely the ahl al-hadith and the ahl al-ra’y. This article addresses two basic questions: first, how is the construction of the method of understanding of both traditions; and second, how is the typology of dialectic hadith understanding between two of them? Based on qualitative-interpretative methods and historical approaches, I argue that the understanding of the hadith of the ahl al-hadith pivots on the rules of al-‘ibrat (fi akhbar al-sunnah bi ‘umum al-lafz la bi khusus al-sabab, while the method of understanding the hadith of the ahl al-ra’y lies on the rules of al-hadith salih li kull zaman wa makan. The typology of understanding of the dialectic hadith between the two groups pivots on the rules of al-‘ibrat (fi akhbar al-sunnah) bi khusus} al-sabab la bi ‘umum al-lafz.